PRARANCANGAN PABRIK ISOPROPIL ASETAT DARI ASAM ASETAT DAN PROPILEN DENGAN KAPASITAS 30.000 TON/TAHUN - , VENITALITYA ALETHEA SARI AUGUSTIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Isopropyl acetate is an ester compound or an organic compound which is produced from esterification of acetic acid and propylene. It is usually used as a solvent in celulose industry, plastic, oil, and fats. It is volatile, so that it is often used in printing ink industry and parfume. The isopropyl acetate from acetic acid and propylene plant is planned to operate 330 days/year and 24 hours/day with capacity 30,000 ton/year. The product obtained is isopropyl acetate with 99.9% purity. This plant will be built in Cilegon, Banten, because the place of the main raw material, which is propylene. Isopropyle acetate is made by esterification of acetic acid and propylene in the bubble reactor. The outside product of reactor are purified using separator drum and distillation vessel to isopropyl acetate with 99.9% purity. The plant is built in 605 acres area and employs 258 employees. This plant requires 2548,2042 kg/hour acetic acid and 1823,0778 kg/hour propylene as the raw material. This plant demands 14143,0748 kg/hour steam, 76232,0238 kg/hour water, and 1842,7692 kVA electricity from generator. From calculation of economic evaluation results, fixed capital required is $17.883.909,11 + Rp 119.156.894.092,14 and working capital required is $365.292,39 + Rp 131.938.317.752,94. At 100% production rate, obtained ROI before tax of 29,25%, ROI after tax of 14,63%, POT before tax of 2,62 years, POT after tax of 4,23 years, with BEP at 45,36%, SDP at 22,96%, and 23,63% for DCFRR. Based on consideration of the economic evaluation results, this isopropyl acetate plant with capacity 30.000 ton/year is worth to be studied further.